An Electron Acceptor Analogue for Lowering Trap Density in Organic Solar Cells. Issue 14 (3rd March 2021) - Zhang, Yihang; Cai, Guilong; Li, Yawen; Zhang, Zhenzhen; Li, Tengfei; Zuo, Xia; Lu, Xinhui; Lin, Yuze
Abstract: Typical organic semiconductor materials exhibit a high trap density of states, ranging from 10 16 to 10 18  cm −3, which is one of the important factors in limiting the improvement of power conversion efficiencies (PCEs) of organic solar cells (OSCs). In order to reduce the trap density within OSCs, a new strategy to design and synthesize an electron acceptor analogue, BTPR, is developed, which is introduced into OSCs as a third component to enhance the molecular packing order of electron acceptor with and without blending a polymer donor. Finally, the as‐cast ternary OSC devices employing BTPR show a notable PCE of 17.8%, with a low trap density (10 15  cm −3 ) and a low energy loss (0.217 eV) caused by non‐radiative recombination. This PCE is among the highest values for single‐junction OSCs. The trap density of OSCs with the BTPR additives, as low as 10 15  cm −3, is comparable to and even lower than those of several typical high‐performance inorganic/hybrid counterparts, like 10 16  cm −3 for amorphous silicon, 10 16  cm −3 for metal oxides, and 10 14 to 10 15  cm −3 for halide perovskite thin film, and makes it promising for OSCs to obtain a PCE of up to 20%. Abstract : A facile strategy of employing an acceptor‐analogue is developed to efficiently reduce trap density to a magnitude of 10 15  cm −3 for organic photovoltaic materials, which is comparable to and even lower than those of some inorganic counterparts, and boosts the power conversion efficiency of organic solar cells up to 17.8%.